The effect of trigger point therapy and medicine ball exercises vs trigger point therapy and stretching on hip rotational biomechanics of the golf swings - S. L. Quinn; B. Olivier; W. Wood; V. Naidoo (AOSIS, 2013)
Background: Elite golfers sustain a large number of lumbar spine injuries. Poor rotational biomechanics, which may occur as a result of a shortened iliopsoas muscle, increase the incidence of lumbar spine injuries in golfers. Stretches and medicine ball exercises are often used as part of golf training programmes in an attempt to restore hip flexor length and improve rotational biomechanics. The aim of this study was to ascertain the effect of a combination of trigger point therapy and medicine ball exercises compared to a combination of trigger point therapy and stretching on rotational bio-mechanics of the golf swing. Method: This is a randomised controlled trial consisting of two experimental groups (trigger point therapy and stretching vs. trigger point therapy and medicine ball exercises) and one control group (no intervention). Hip flexor length and 3D biomechanical analysis of the golf swing was performed at baseline and one week later. Results: One-hundred elite male golfers participated in this study. Rotational biomechanics, specifically downswing hip turn in the group that received trigger point therapy combined with medicine ball exercises, showed statistically significant improvement at reassessment compared to the control group (p=0.0328). Conclusion: Rotational biomechanics (downswing hip turn) improved following a combination of trigger point therapy treatment and a one week programme of medicine ball exercises. This is postulated to have occurred through neural reorganisation and not through improved tensile muscle strength. This improvement in rotational biomechanics has the potential to decrease lumbar spine injury incidence in elite golfers. This study advocates the use of trigger point therapy combined with medicine ball exercises in the treatment of golfers with shortened hip flexors.